PENGARUH PELAKSANAAN PAÑCASĪLA BUDDHIS DAN PAÑCADHAMMA TERHADAP PEMBENTUKAN KARAKTER BUDDHIS SISWA SMP MAITREYAWIRA BATAM - Sugianto, Sugianto; Khie Khiong; Julia surya (LPSDI Bina Patria, 2024)
This study seeks to quantify the impact of implementing Buddhist Pañcasīla and Pañcadhamma on the development of Buddhist character in eighth-grade students at Maitreyawira Junior High School in Batam. A quantitative approach was employed, using a survey method with a causality model. The subject group for this study consisted of 300 students in class VIII at Maitreyawira Junior High School in Batam. The sample of this research is all Buddhist students of class VIII which amounted to 177 students. The sampling technique was carried out using sampling with simple random sampling. Data collection techniques using a questionnaire. Assumption test uses normality, linearity, heteroscedasticity, and multicollinearity tests.The data analysis reveals a significant influence between the variables of Buddhist pañcasīla and Pañcadhamma implementation on the formation of Buddhist character. Thus, it is evident that the implementation of Buddhist pañcasīla and Pañcadhamma have significant effects on the formation of Buddhist character. The regression coefficient of the Buddhist pañcasīla variable (X1) is 2.5% or 0.025, whereas the Pañcadhamma variable (X2) shows a regression of 0.006 or 6%. Based on the coefficient of determination test, the Adjusted R square value is 0.008%. This indicates that only 8% of Buddhist Pañcasīla (X1) and Pañcadhamma (X2) variables can account for the variation in the variable of Buddhist character formation (Y) in Batam's Maitreyawira Junior High School students. The remaining 92% is attributed to the regression test.The study concludes that Buddhist principles such as Pañcasīla (X1) and Pañcadhamma (X2), along with the development of Buddhist character, significantly impact the formation of Buddhist character within Maitreyawira Junior High School students in Batam. The recommendation is for students to further develop the application of Buddhist Pañcasīla (X1) and Pañcadhamma (X2) beyond school and into their homes. It is also suggested that other researchers conduct more in-depth studies on these subjects